Treatment of ongoing autoimmune encephalomyelitis with activated B-cell progenitors maturing into regulatory B cells - Sarantis Korniotis (Nature Portfolio, 2016)
Evidence of how functional Bregs develop in vivo has been lacking. Here the authors show that proB cells exposed in vivoto CpG differentiate into distinct Breg subsets that inhibit autoimmunity by arresting T cells in the lymph nodes via CCL19 and by producing IL-10 at the site of immunopathology.